Optimum location and relocation plan of semi-mobile in-pit crushing and conveying systems in open-pit mines by transportation problem. Issue 5 (4th July 2019) - Abbaspour, Hossein; Drebenstedt, Carsten; Paricheh, Morteza; Ritter, Robert
Abstract: In-pit crushing and conveying (IPCC) systems have attracted more interest among miners as an alternative to the conventional truck-shovel transportation system. The semi-mobile IPCC (SMIPCC) system is a well-suited type of IPCC system in open-pit mining projects because of its relocation nature. However, it is very important to design its optimum location and relocation plan in a manner that minimises the operating costs. In spite of a few previous works, which propose methods for optimum location and time in order to shift from a truck-shovel system to an IPCC system, a combined optimum location and relocation plan of the SMIPCC has not been investigated. This paper defines the optimum location and relocation plan of the SMIPCC in the context of a transportation problem with different 'year levels' as the sources and 'levels' as the destinations. This model is able to calculate the optimum solution simultaneously in the case of both location (level) and time (year level). The results show that this method can efficiently be applied as a planning tool for optimising operating and relocation costs, and the location and relocation plan of the SMIPCC.